Sheath cable

The sea skable's two-layer structure with a wood-based inner layer and ethylene polymer outer layer effectively controls adhesion, addressing peeling issues and maintaining a smooth surface, enhancing peeling manageability and cost-effectiveness.

JP2025011850APending Publication Date: 2025-01-24YAZAKI ENERGY SYSTEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023114216
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing sea skables face difficulties in controlling adhesion between the insulating wire and sheath, leading to peeling issues and deterioration of the skin due to high adhesion strength, which is exacerbated by the application of flowing paraffin and PVC paste gel.

Method used

A sea skable design with a sheath composed of at least two layers, where the inner layer is made of wood-based materials like crushed rice husk, bamboo, or shells, and the outer layer is composed of ethylene polymer, ensuring a thickness of 0.2 mm or more for the inner layer to maintain uniform adhesion and prevent exposure of the wood-based material, thereby controlling adhesion to 20 N/10 mm or less.

Benefits of technology

The design allows for easy control of adhesion between the insulated wire and sheath, ensuring peeling is manageable and maintaining a smooth surface, while also being environmentally friendly and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011850000001_ABST
    Figure 2025011850000001_ABST
Patent Text Reader

Abstract

To provide a sheath cable capable of making it easy to control in a state where adhesion between an insulated wire and a sheath is totally low.SOLUTION: A sheath cable 1 is provided with a sheath 20 in contact on an insulated wire 10, and the sheath 20 is composed of having at least two or more layers, and an innermost layer 21 has a thickness of 0.2 mm or more and composed including a wood-based material made of at least one of crushed rice husks, wood, bamboo, and coconut husks. The adhesion force between the insulated wire 10 and the sheath 20 is 20 N / 10 mm or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheathed cable. [Background technology]

[0002] Conventionally, sheathed cables in which an insulated electric wire is covered with a sheath have been proposed. For this sheathed cable, it has been proposed to apply liquid paraffin or gelled PVC paste between the insulated electric wire and the sheath in order to improve the peelability between them (to reduce the adhesion) (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 2879289 [Patent Document 2] Patent No. 3070817 Summary of the Invention [Problem to be solved by the invention]

[0004] Here, the sheathed cables described in Patent Documents 1 and 2 require a process of stripping the insulator and sheath of the insulated wire at the cable end. However, if the insulator and sheath are in close contact with each other too much, stripping becomes difficult, resulting in poor stripping properties.

[0005] Therefore, as described in Patent Documents 1 and 2, the application of liquid paraffin or the like between the insulator and sheath, which reduces the adhesion between the two, has been considered. However, it is difficult to apply liquid paraffin or the like evenly, and there may be some areas with high adhesion and some areas with low adhesion. For this reason, the adhesion at the stripping point may happen to be high, which results in poor stripping properties. Therefore, a sheathed cable in which the adhesion between the insulator and sheath is controlled to be low overall is desired.

[0006] The present invention has been made to solve such problems, and its object is to provide a sheathed cable in which it is easy to control the adhesion between the insulated wire and the sheath to a low level overall. [Means for solving the problem]

[0007] The sheathed cable of the present invention is a sheathed cable having a sheath provided in contact with an insulated electric wire, the sheath being composed of at least two layers, the innermost layer having a thickness of 0.2 mm or more and containing a wood-based material made of at least one of crushed rice husks, wood, bamboo, and coconut shells, and the adhesion strength between the insulated electric wire and the sheath is 20 N / 10 mm or less. Effect of the Invention

[0008] According to the present invention, it is possible to provide a sheathed cable in which the adhesion between the insulated wire and the sheath can be easily controlled to a low state overall. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a perspective view of a sheath cable according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an end view of the sheath cable shown in FIG. [Diagram 3] 3 is an enlarged end view showing the boundary between the insulated wire and the sheath shown in FIG. 2. [Figure 4] 1 is a table showing examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described below along with preferred embodiments. Note that the present invention is not limited to the embodiments shown below, and can be modified as appropriate within the scope of the present invention. In addition, in the embodiments shown below, some configurations are omitted from illustration and description, but it goes without saying that publicly known or well-known technologies are appropriately applied to the details of the omitted technologies within the scope of the contents described below.

[0011] Fig. 1 is a perspective view of a sheathed cable according to an embodiment of the present invention, and Fig. 2 is an end view of the sheathed cable shown in Fig. 1. The sheathed cable 1 shown in Figs. 1 and 2 includes an insulated wire 10 and a sheath 20.

[0012] The insulated wire 10 is formed by covering a conductor 11 with an insulator 12. The conductor 11 may be, for example, a soft copper wire, a silver-plated soft copper wire, a tin-plated soft copper wire, or a tin-plated copper alloy wire. In the present embodiment, the conductor 11 is illustrated as being made of a single solid wire, but the present invention is not limited to this and may be made of a twisted wire in which two or more strands are twisted together. The insulator 12 is a member that covers the conductor 11, and may be made of, for example, PE (Polyethylene) or PP (Polypropylene).

[0013] The sheath 20 is provided on the outside of the insulated wire 10 in contact with the insulated wire 10. The sheath 20 is preferably made of an insulating material containing, for example, PE as a main component.

[0014] In this embodiment, the sheath 20 is configured to have two or more layers in the radial direction from the inside to the outside. In the following description, the sheath 20 will be described as having a two-layer structure, but in the case of a structure having three or more layers, one or more intermediate layers are interposed between the innermost layer 21 and the outermost layer 22 described later.

[0015] The sheath 20 according to this embodiment has an innermost layer 21 and an outermost layer 22. The innermost layer 21 and the outermost layer 22 have different configurations, and the innermost layer 21 is configured to contain a wood-based material (see symbol WM in FIG. 3 described later) made of at least one of crushed rice husks, wood, bamboo, and coconut shells. On the other hand, the outermost layer 22 is configured to not contain such a wood-based material.

[0016] Fig. 3 is an enlarged end view showing the boundary B between the insulated wire 10 and the sheath 20 shown in Fig. 2. As shown in Fig. 3, the innermost layer 21 of the sheath 20 contains at least a predetermined amount (appropriate amount) of wood-based material WM. As a result, a part of the wood-based material WM protrudes from the resin surface of the innermost layer 21. As a result, the sheath 20 is in contact with the insulated wire 10 via the wood-based material WM. Therefore, although the sheath 20 is in contact with the insulated wire 10, it is not in close contact with the insulated wire 10.

[0017] In addition, in the sheath cable 1 shown in Figs. 1 to 3, the innermost layer 21 has a thickness of 0.2 mm or more. When the innermost layer 21 of the sheath 20 is manufactured by extrusion molding or the like, if the innermost layer 21 has a thickness of 0.2 mm, the thickness can be made approximately uniform. If the thickness is not uniform, the amount of wood-based material WM in each part of the innermost layer 21 may vary, and some parts may be in close contact with the insulated electric wire 10 and some parts may not be in close contact at all. This results in some parts having high adhesion and some parts having low adhesion, making it difficult to control the adhesion between the sheath 20 and the insulated electric wire 10 to be generally low. However, by making the innermost layer 21 to have a thickness of 0.2 mm or more, the thickness of the innermost layer 21 can be made uniform, making it difficult to cause differences in the amount of wood-based material WM, and controlling the adhesion between the sheath 20 and the insulated electric wire 10 to be generally low.

[0018] The content of the wood-based material WM is preferably set according to the average particle size of the wood-based material WM. In this embodiment, the average particle size of the wood-based material WM is assumed to be 100 μm or more and 1500 μm or less, and the sheath cable 1 contains an appropriate amount or more of the wood-based material WM with such an average particle size, so that the adhesion strength is set to a predetermined value or less. For reference, the innermost layer 21 can have the adhesion strength set to a predetermined value or less by containing 50% by weight or more of the wood-based material WM with an average particle size of 100 μm or more and 1500 μm or less relative to 100% by weight of PE.

[0019] Here, it is preferable that the outermost layer 22 of the sheath 20 also has a thickness of 0.2 mm or more. This is because the thickness of the outermost layer 22 can be made approximately uniform. If the thickness of the outermost layer 22 is not ensured to be 0.2 mm or more, the thickness will be non-uniform. In this case, the outermost layer 22 will have extremely thin parts, and the wood-based material WM may be exposed in those parts, impairing the smoothness (moldability) of the surface of the sheath 20. However, by making the outermost layer 22 0.2 mm or more thick, the thickness of the outermost layer 22 can be made uniform, and good moldability can be achieved.

[0020] The upper limit of the thickness of the innermost layer 21 is not particularly determined, but when the thickness of the outermost layer 22 is set to 0.2 mm or more, it is set to a range that allows the thickness of the outermost layer 22 to be ensured. For example, when the sheath thickness is 2.0 mm and a thickness of 0.2 mm is to be ensured for the outermost layer 22, the upper limit of the thickness of the innermost layer 21 is set to 1.8 mm, which is (sheath thickness) - (outermost layer thickness).

[0021] It is preferable that the innermost layer 21 and the outermost layer 22 have the same composition except for the presence or absence of a wood-based material. This is because peeling between the resins at the boundary between the innermost layer 21 and the outermost layer 22 can be easily suppressed.

[0022] Furthermore, the sheath 20 preferably contains 20% by weight to 100% by weight of ethylene copolymer relative to 100% by weight of PE, and the content of monomers other than ethylene in the ethylene copolymer is preferably 15% by weight to 35% by weight. In this case, the wood-based material WM of the sheath 20 is preferably 150% by weight or less. This is because such a configuration makes it possible to achieve a balance between the desired tensile elongation, moldability, environmental friendliness, and cost.

[0023] Next, a method for manufacturing the sheathed cable 1 according to the present embodiment will be described. In manufacturing the sheathed cable 1, first, an insulated wire 10 is manufactured. At this time, a predetermined insulator 12 is extrusion-molded onto a predetermined conductor 11, thereby manufacturing the insulated wire 10.

[0024] Furthermore, while the insulated wire 10 is being manufactured, a resin constituting the sheath 20 is prepared. Here, for example, PE is used for the outermost layer 22, and for the innermost layer 21, a wood-based material WM is added to the PE constituting the outermost layer 22. Here, when the average particle size of the added wood-based material WM is 100 μm or more and 1500 μm or less, 50% by weight or more of the wood-based material WM is added to 100% by weight of PE.

[0025] The wood-based material WM to be added may be surface-treated with fatty acid or silane coupling agent to improve adhesion to the resin (PE). After adding the wood-based material WM to the resin, it is preferable to knead the material at a temperature of 150°C or higher for 5 minutes or more. This is because the residual moisture in the wood-based material WM can be reduced.

[0026] Furthermore, in order to achieve a balance between tensile elongation, moldability, environmental friendliness, and cost, the ethylene copolymer may contain 20% by weight or more and 100% by weight or less of an ethylene copolymer having a content of monomers other than ethylene of 15% or more and 35% or less, relative to 100% by weight of PE, and the wood-based material WM may contain 150% by weight or less.

[0027] Thereafter, the innermost layer 21 is extrusion molded on the insulated wire 10. At this time, the thickness of the innermost layer 21 is set to 0.2 mm or more. Next, if one or more intermediate layers are provided, the intermediate layers are extrusion molded, and then the outermost layer 22 is extrusion molded. The thickness of the outermost layer 22 is preferably set to 0.2 mm or more. In this manner, the sheathed cable 1 is manufactured.

[0028] Next, examples and comparative examples will be described. Fig. 4 is a table showing examples and comparative examples. Note that in the examples and comparative examples, rice husks (crushed) with an average particle size of 100 μm to 1500 μm are used as the wood-based material, but the present invention is not limited to rice husks.

[0029] First, in Example 1, the sheath resin used was 100% by weight PE and 20% by weight of ethylene copolymer with 15% content of monomers other than ethylene. The innermost layer was further added with 50% by weight of crushed rice husk. The sheath had a two-layer structure with an innermost layer and an outermost layer, with the innermost layer being 0.2 mm thick and the outermost layer being 1.8 mm thick.

[0030] In Example 2, the sheath resin used was 100% by weight PE and 50% by weight of ethylene copolymer with 20% content of monomers other than ethylene. The innermost layer was further added with 60% by weight of crushed rice husk. The sheath had a two-layer structure with an innermost layer and an outermost layer, with the innermost layer being 0.5 mm thick and the outermost layer being 0.5 mm thick.

[0031] In Example 3, the sheath resin used was a mixture of 100% by weight of PE and 100% by weight of ethylene copolymer with 35% content of monomers other than ethylene. The innermost layer was further mixed with 150% by weight of crushed rice husk. The sheath had a two-layer structure consisting of an innermost layer and an outermost layer, with the innermost layer being 1.8 mm thick and the outermost layer being 0.2 mm thick.

[0032] In Example 4, PE was used as the sheath resin. Ethylene copolymer was not used. The innermost layer was made of crushed rice husks at 60% by weight. The sheath had a two-layer structure with an innermost layer and an outermost layer, with the innermost layer being 0.2 mm thick and the outermost layer being 1.8 mm thick.

[0033] In Example 5, the sheath resin used was a mixture of 100% by weight of PE and 100% by weight of ethylene copolymer with a non-ethylene monomer content of 35%. The innermost layer was further mixed with 170% by weight of crushed rice husk. The sheath had a two-layer structure consisting of an innermost layer and an outermost layer, with the innermost layer being 0.2 mm thick and the outermost layer being 1.8 mm thick.

[0034] In Example 6, the sheath resin used was a mixture of 100% by weight PE and 120% by weight of ethylene copolymer with 25% content of monomers other than ethylene. The innermost layer was further mixed with 60% by weight of crushed rice husk. The sheath had a two-layer structure consisting of an innermost layer and an outermost layer, with the innermost layer being 2.0 mm thick and the outermost layer being 0.2 mm thick.

[0035] In Example 7, the sheath resin used was 100% by weight PE and 50% by weight of ethylene copolymer with 10% content of monomers other than ethylene. The innermost layer was further added with 60% by weight of crushed rice husk. The sheath had a two-layer structure with an innermost layer and an outermost layer, with the innermost layer being 2.0 mm thick and the outermost layer being 2.0 mm thick.

[0036] In Example 8, the sheath resin used was 100% by weight PE and 50% by weight of ethylene copolymer with 40% content of monomers other than ethylene. The innermost layer was further added with 60% by weight of crushed rice husk. The sheath had a two-layer structure with an innermost layer and an outermost layer, with the innermost layer being 1.8 mm thick and the outermost layer being 0.2 mm thick.

[0037] In Example 9, the sheath resin used was a mixture of 100% by weight of PE and 100% by weight of ethylene copolymer with 35% content of monomers other than ethylene. The innermost layer was further mixed with 150% by weight of crushed rice husk. The sheath had a two-layer structure consisting of an innermost layer and an outermost layer, with the innermost layer being 1.9 mm thick and the outermost layer being 0.1 mm thick.

[0038] In Comparative Example 1, the sheath resin used was a mixture of 100% by weight PE and 100% by weight ethylene copolymer with 25% content of monomers other than ethylene. The innermost layer was further mixed with 30% by weight of crushed rice husk. The sheath had a two-layer structure consisting of an innermost layer and an outermost layer, with the innermost layer being 0.2 mm thick and the outermost layer being 1.8 mm thick.

[0039] In Comparative Example 2, the sheath resin used was a mixture of 100% by weight of PE and 100% by weight of ethylene copolymer with 35% content of monomers other than ethylene. The innermost layer was further mixed with 150% by weight of crushed rice husk. The sheath had a two-layer structure consisting of an innermost layer and an outermost layer, with the innermost layer being 0.1 mm thick and the outermost layer being 1.9 mm thick.

[0040] An adhesion test was performed on the above-mentioned Examples 1 to 9 and Comparative Examples 1 and 2. In the adhesion test, the sheath of the extrusion-molded sheath cable was cut with a cutter knife so as to divide it into two equal parts, and one of the two divided sheaths was peeled off by about 50 mm to prepare a test piece. The test piece was set in an Intesco tabletop precision universal material testing machine and a tensile test was performed. One end of the tensile test chucked the insulated wire, and the other end was folded back 30 mm (180° folded back) after peeling off the 50 mm in two, and the tip of the folded back was chucked. The tensile test was performed in accordance with JIS C 3005:2014, at a tensile speed of 200 mm / min, at a temperature (room temperature) of about 23°C, and with a gripping distance of 80 mm, with the number of tests being n=3. The maximum load for each test was measured, and those with an average of 3 tests of 20N / 10mm or less were deemed to have passed (marked "O" in Figure 4), and those with an average of more than 20N / 10mm were deemed to have failed (marked "X" in Figure 4). Note that those with an average of 20N / 10mm or less were deemed to have passed because they also had good peeling workability.

[0041] As a result of the above test, the adhesion strength was 20N / 10mm or less for all of Examples 1 to 9. In contrast, for Comparative Example 1, the amount of crushed rice husk blended was insufficient at less than 50% by weight, so the adhesion strength between the insulated wire and the sheath could not be controlled low, resulting in an adhesion strength exceeding 20N / 10mm. For Comparative Example 2, although the amount of crushed rice husk blended was sufficient, it was difficult to make the thickness of the innermost layer uniform because the thickness was 0.1mm, and there were parts with high adhesion and parts with low adhesion, resulting in an overall adhesion strength exceeding 20N / 10mm.

[0042] From the above, it was found that the innermost layer needs to contain more than the appropriate amount of rice husk (wood-based material), and if the thickness of the innermost layer is 0.2 mm or more, the adhesion force can be made 20 N / 10 mm or less.

[0043] Furthermore, the tensile elongation was tested as follows. First, the extrusion-molded sheath was punched out with a super dumbbell cutter SDK-300 manufactured by Dumbbell Co., Ltd. while keeping the original thickness of 1.5 mm, to prepare a dumbbell-shaped No. 3 tensile test piece conforming to JIS K6251:2017. The tensile test was performed using an Intesco tabletop precision universal material testing machine conforming to JIS C3005:2014, with a tensile speed of 200 mm / min, a temperature (room temperature) of about 23°C, a gauge length of 20 mm, and a grip length of 50 mm, with the number of tests being n=3. The tensile elongation (%) was measured in each test, and a test with an average value of 340% or more was deemed to have passed ("◯" in FIG. 4), and a test with an average value below 340% was deemed to have failed ("×" in FIG. 4).

[0044] Regarding moldability, we checked whether the extrusion load during extrusion molding was within the normal range, whether the thickness was uniform (within 10% of the difference between the maximum and minimum thickness), whether the outer surface of the sheath was smooth, and whether the sheath was carbonized. If there were no problems with any of these, the product was rated as passed ("O" in Figure 4), and if there was a problem with any one of them, the product was rated as failed ("X" in Figure 4).

[0045] Furthermore, from an environmental perspective, if the amount of rice husk, a wood-based material, used was equal to or greater than the specified amount, it was deemed to have passed ("O" in Figure 4), and if it was less than the specified amount, it was deemed to have failed ("X" in Figure 4).

[0046] The cost aspect was judged based on the amount of ethylene copolymer used. Since ethylene copolymer is expensive, if the amount of ethylene copolymer used was below a certain amount, it was judged as pass ("O" in Figure 4), and if it exceeded the certain amount, it was judged as fail ("X" in Figure 4).

[0047] When such evaluation was performed, Examples 1 to 3 passed all four items of tensile elongation, moldability, environmental aspects, and cost, while Examples 4 to 9 and Comparative Examples 1 and 2 failed in one or more of the four items.

[0048] As shown in Examples 1 to 3 above, it was found that if the following three conditions are met, the four items will pass. The first condition is that the material contains 20% by weight to 100% by weight of ethylene copolymer with a content of monomers other than ethylene of 15% to 35% relative to 100% by weight of PE. The second condition is that the material contains 50% by weight to 150% by weight of crushed rice husk. The third condition is that the thickness of the outermost layer is 0.2 mm or more.

[0049] On the other hand, in Example 4, since the ethylene copolymer itself was not contained, the adhesion between the resin and the rice husks was reduced, and the tensile elongation was unacceptable.

[0050] In Example 5, the amount of rice husk was too much, and the ratio of resin was reduced, resulting in failure in tensile elongation. Furthermore, in Example 5, the amount of rice husk was too much, and the extrusion load exceeded the normal range, which led to a decrease in the smoothness of the outer surface of the sheath, and the moldability was also unacceptable.

[0051] Example 6 was rejected due to the excessive amount of ethylene copolymer, which was disadvantageous from the standpoint of cost.

[0052] In Example 7, since the content of monomers other than ethylene in the ethylene copolymer was low, the adhesion between the resin and the rice husks decreased, and the tensile elongation failed the test.

[0053] In Example 8, since the ethylene copolymer had a high content of monomers other than ethylene, the adhesion to the extruder and the like increased, and the resin remaining in the extruder was carbonized, resulting in unacceptable moldability.

[0054] In Example 9, the outermost layer did not ensure a thickness of 0.2 mm, and there was a problem with uniformity, so that the innermost layer was exposed in some places, and the moldability was unacceptable.

[0055] Furthermore, Comparative Example 1 failed in adhesion and also failed in environmental considerations due to the small amount of rice husk used. Similarly, Comparative Example 2 also failed in environmental considerations due to the absolute amount of rice husk used being small as the innermost layer became thinner.

[0056] In this way, according to the sheath cable 1 of the present embodiment, the sheath 20 is configured to have at least two or more layers, and the innermost layer 21 is configured to contain a wood-based material WM made of at least one of crushed rice husks, wood, bamboo, and coconut shells. Therefore, the innermost layer 21 in contact with the insulated electric wire 10 contains the wood-based material WM, and as a result of the wood-based material WM coming into contact with the insulated electric wire 10, the insulator 12 of the insulated electric wire 10 and the sheath 20 are unlikely to come into close contact with each other. In particular, by having such a configuration and mixing an appropriate amount of rice husks or the like to make the adhesion force 20 N / 10 mm or less, the adhesion force can be controlled to a degree that makes the peeling property good. Moreover, since the thickness of the innermost layer 21 is 0.2 mm or more, the thickness is secured to a certain extent and is easily made uniform, and it is also possible to prevent, for example, the thickness becoming too thin in some parts, which locally reduces the amount of rice husks or the like to be mixed, making it difficult to control the adhesion force. Therefore, it is possible to provide a sheathed cable 1 in which the adhesion between the insulated wire and the sheath can be easily controlled to a low state overall.

[0057] The innermost layer 21 is thick enough to ensure that the outermost layer 22 has a thickness of 0.2 mm or more. This prevents the innermost layer 21 from becoming too thick to the point where the thickness of the outermost layer 22 cannot be ensured, and also suppresses the possibility that the wood-based material WM of the innermost layer 21 will be exposed due to the innermost layer 21 being too thin, thereby ensuring the smoothness of the surface.

[0058] The present invention has been described above based on an embodiment, but the present invention is not limited to the above embodiment, and modifications may be made or well-known and publicly known technologies may be combined without departing from the spirit of the present invention.

[0059] For example, in the above embodiment, the sheathed cable 1 has been described as having a two-layer structure, but the structure is not limited to a two-layer structure, and the sheathed cable 1 may have three or more layers. Furthermore, in the above embodiment, the insulated wire 10 is one, but the structure is not limited to this, and the insulated wire 10 may be two or more. [Explanation of symbols]

[0060] 1: Sheathed cable 10: Insulated wire 11: Conductor 12: Insulator 20: Sheath 21: Innermost layer 22: Outermost layer WM: Wood-based materials

Claims

1. A sheathed cable in which a sheath is provided on an insulated electric wire in contact with the insulated electric wire, The sheath is configured to have at least two or more layers, and the innermost layer has a thickness of 0.2 mm or more and is configured to include a wood-based material made of at least one of crushed rice husks, wood, bamboo, and coconut shells; The adhesive strength between the insulated wire and the sheath is 20 N / 10 mm or less. A sheathed cable comprising:

2. the sheath has a two-layer structure including the innermost layer and an outermost layer that is substantially free of wood-based materials, The outermost layer has a thickness of 0.2 mm or more, The innermost layer is thick enough to ensure that the outermost layer of the sheath has a thickness of 0.2 mm or more.

2. The sheathed cable according to claim 1 .

Citation Information

Patent Citations

  • Vinyl-insulated vinyl-sheathed cable and its manufacturing method

    JP2879289B2

  • Highly peelable vinyl-insulated vinyl-sheathed cable and method for producing highly peelable vinyl-insulated vinyl-sheathed cable

    JP3070817B2